Isolation and Characterization of Mushroom Growth Promoting Bacteria from Spent Mushroom Compost of Lentinula edodes - Rana, Neerja; Sharma, Prachi; Chauhan , Shivani; Ghabru, Arti (International Journal of Economic Plants, 2025)
The experiment was conducted from November, 2022 to June, 2023 in the laboratory of Department of Basic Sciences and in the Mushroom unit, Department of Plant Pathology of Dr. YS Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India, to study the isolation and characterization of mushroom growth promoting bacteria from spent mushroom compost of Lentinula edodes. The mushroom growth promoting bacteria (MGPB) stimulate mycelial growth and fruiting by enhancing nutrient elements concentration, protein and carbohydrate contents. The spent mushroom compost can be a good source of growth promoting bacteria for mushroom cultivation. For the present investigation, samples of spent mushroom compost (SMC) were collected from two locations of Solan i.e., Directorate of Mushroom Research, Chambaghat and University of Horticulture and Forestry (UHF), Nauni. A total of 45 bacterial isolates were isolated from SMC and purified for further studies. Out of 45 bacterial isolates, 28 were P-solubilizers, 29 were nitrogen fixers, 19 were HCN producers, 22 were siderophore producers and 23 were IAA producers. Out of 45 bacterial isolates only 3 isolates were selected based on multifarious PGPR traits. Among the selected bacterial isolates, maximum P-solubilization was shown by isolate DMR1-36, both qualitatively and quantitatively. Maximum siderophore production efficiency (SE%) was observed in isolate DMR1-36 on solid CAS medium as well as in case of liquid medium. Bacterial isolate DMR1-36 showed highest production of IAA. All three bacterial isolates showed maximum growth at temperature of 35°C, pH 7.0 and incubation period of 48 hours.